Rancang Bangun Aplikasi Monitoring Kegiatan MBKM & Prestasi Mahasiswa Menggunakan Algoritma Lempel ZIV Welch (LZW) untuk Kompresi Citra Digital - Novantara, Panji; Sugiharto, Tito; Priantama, Rio (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The MBKM (Merdeka Learning Kampus Merdeka) activity is part of the Merdeka Learning policy which allows students and lecturers to carry out various activities outside the campus. This study aims to design an application for monitoring MBKM activities and student achievement at the Faculty of Computer Science, University of Kuningan. The application development model used in this study is a prototyping model with stages: needs analysis, building prototyping, evaluating prototyping, system coding and using the system. In the process of storing evidence of MBKM activity documentation such as MBKM photos & certificates of achievement & MBKM, an image compression technique is needed to streamline data storage and transmission which saves bandwidth and storage, image file compression techniques are applied using the LZW algorithm (Lempel Ziv Welch) so that data file storage is more efficient. efficiently without reducing image quality. The results of this study are an application for monitoring MBKM activities and student and lecturer achievements that aim to document & evaluate MBKM activities & achievements at the Faculty of Computer Science, University of Kuningan, making it easier to report MBKM activities and lecturer & student achievements.